CHLORITIC ROCKS AND CHLORITIZED BASALTS AS PLAUSIBLE PRECURSORS OF METAMORPHIC PERIDOTITES AND PYROXENITES IN THE KOKCHETAV MASSIF, NORTHERN KAZAKHSTAN - Reverdatto V.V.; Selyatitskiǐ A.Yu. (My University, 2004)
Inordinary and similar chemical composition of garnet peridotites and spinel harzburgites allows suggesting that they were formed from chlorite rocks contained in the upper part of Earth crust. Submerging to the depth of 100-150 km upon subduction has lead to metamorphism of these rocks. Associating with harzburgites pyroxenites were formed on the base of chloritized basalts, as concluded from geological and geochemical data analysis.